BEHAVIORAL ANALYSIS OF STUDENTS' CREATIVE THINKING ABILITY IN LEARNING MATHEMATICS - Nurazizah Ramadhini; Abdurrahman; Wahyuni, Reni; Suripah (UIR PRESS, 2023)
The purpose of this research is to explain the ability of students' creative thinking in learning mathematics in regards to their behavior in class VIII. This is a descriptive qualitative research. Written tests and questionnaire procedures were utilized to gather data. A number of data analysis methods have been employed in this research: (1) data collecting; (2) data reduction; (3) data presentation; and (4) conclusion drawing. This study concentrated on four elements: (1) fluency; (2) flexibility; (3) originality; and (4) elaboration. According to the findings of this research, the creative thinking ability of grade VIII students is included as part of the creative category with an average percentage of 63.75%. While the attitude of grade VIII pupils is regarded as good, with an average percentage of 73.10%. In the creative thinking ability as good, students with a positive attitude have a creative thinking rate of 63.19%. Overall, students with very good and good attitudes have creative thinking ability.